Corn intercropped with tropical perennial grasses as affected by sidedress nitrogen application rates - Mateus, G. P.; Crusciol, C. A.C. [UNESP]; Pariz, C. M. [UNESP]; Costa, N. R. [UNESP]; Borghi, E. [UNESP]; Costa, C. [UNESP]; Martello, J. M. [UNESP]; Castilhos, A. M. [UNESP]; Franzluebbers, A. J.; Cantarella, H. (Springer Nature, 2020)
In tropical regions, one of the primary difficulties in the sustainability of no-till systems is the maintenance of soil cover throughout the year. Intercropping corn (Zea mays L.) with tropical perennial grasses is an innovative approach to overcome this difficulty. However, the use of sidedress nitrogen (N) fertilization in this intercropping system remains incompletely studied. The effects of using sidedress N application rates (0, 50, 100 and 200 kg ha−1 N) on monocropped corn or corn intercropped with palisadegrass [Urochloa brizantha (Hochst. ex A. Rich.) R. Webster ‘Marandu’] or guineagrass [Megathyrsus maximum (Jacq.) R. Webster ‘Mombaça’] with respect to leaf nutrient concentration, agronomic characteristics, revenue and land use efficiency were investigated over three growing seasons in the Brazilian Cerrado region on a clay soil, kaolinitic, thermic Typic Haplorthox. In general, the intercropping systems of corn with palisade or guineagrass did not cause reductions in the leaf nutrient concentration, agronomic characteristics, kernels attributes, shoot dry matter and corn yield compared to that observed in the monocropped system. High sidedress N application rates promoted higher concentrations of nutrients in leaves (primarily N and P), corn yield, forage production and crude protein concentration in the off-season. Corn monocropped or intercropped with palisadegrass and guineagrass using 113, 156 and 187 kg ha−1 N resulted in the highest corn yields (9.2, 8.8 and 9.7 Mg ha−1, respectively). In addition, using these N application rates, corn intercropped with palisadegrass and guineagrass and subsequent meat production estimated on pastures resulted in the highest net profits (US$ 1196 and 1093 ha−1, respectively), whereas monocropped corn without N addition resulted in the lowest net profits (US$ 304 ha−1). Thus, forage produced during the off-season can be used for animal grazing or fodder during the dry season, increasing revenue. Corn intercropped with palisade grass with the addition of 200 kg ha−1 N resulted in a higher land equivalent ratio and relative N yield (1.21 and 123%, respectively). In summary, sidedress N fertilization in intercropped systems can increase crop and forage yields and revenue, improving land-use efficiency in tropical agriculture.
Keywords: Intercropping crops; Megathyrsus maximum; No-tillage system; Sustainable tropical agriculture; Urochloa brizantha; Zea mays L